Responses to long-term fertilization and burning: impacts on nutrient dynamics and microbial composition in a tallgrass prairie - Carson, Michael A. (Kansas State University, 2013)
Anthropogenic activities impact ecosystems in numerous direct and indirect ways, affecting the cycling of carbon (C) and nitrogen (N) on local, regional and global scales. North America tallgrass prairie is an ecosystem profoundly altered by anthropogenic activities, with most native prairie converted to alternate land uses or heavily impacted by other environmental changes. While aboveground responses to anthropogenic drivers have received much attention, the responses of belowground biota, ecological processes, and nutrient allocation to land management and environmental change are poorly documented, especially over long timeframes. This research builds upon a long-term experiment (the Belowground Plot Experiment) initiated in 1986 at Konza Prairie Biological Station (Manhattan, KS). I utilized a subset of treatments to address the effects of annual burning vs. fire suppression and/or chronic N additions on soil C and N dynamics and microbial communities in tallgrass prairie. I measured a suite of soil variables related to C and N cycling during the 2012 growing season, including total soil C and N, microbial biomass C and N, in situ net N mineralization, potential N mineralization, in situ CO2 efflux, and potentially mineralizable soil C. I also assessed changes in microbial community composition using microbial phospholipid fatty acids (PLFA) profiles. Annual burning significantly (p≤0.05) increased the soil C:N ratio and in situ CO2 efflux, while decreasing potential ammonification and nitrification rates. Annual burning also increased total PLFA mass and relative abundance of fungi. Chronic N addition (100 kg N ha-1 year-1) significantly reduced the soil C:N ratio, while increasing total soil N and potential nitrification and ammonification rates. Chronic N addition reduced potential C mineralization, microbial biomass C and N, and altered microbial community composition by increasing abundance of bacterial PLFAs and reducing fungal PLFAs. Sampling date also significantly affected many variables. These results indicate that different fire regimes and chronic N enrichment over decades affects soil C and N pools and transformations, as well as microbial biomass and composition. In total, this study highlights the importance of long-term ecological research and identifies likely changes in tallgrass prairie nutrient dynamics and soil microbial communities under increased N and frequent burning.
Keywords: Carbon; Nitrogen; Tallgrass Prairie; Soil ecology; Biogeochemistry; Biogeochemistry (0425); Biology (0306); Environmental Sciences (0768); Soil Sciences (0481)